laser vs optical urethrotomy for urethral stricture - Ali Haseeb; Mahmood karbalaie (Basrah Journal of Surgery, 2021)
A urethral stricture is a scar of the subepithelial tissue of the corpus spongiosum that constricts the urethral lumen. As the constriction increases, obstruction occurs and leads to symptoms which may be related to the obstruction or secondary to it(1). (Figure 1). The term stricture usually used for constrictions of the anterior urethra. Otherwise in the posterior urethra the terms stenosis or contracture are applied(2). The site and the age of the patient may give a hint about the cause of the stricture. For example, Meatal strictures may be caused by lichen sclerosis (the most common identifiable cause of anterior urethral stricture in young adults), and instrumentation or poor hygiene at any age(2) A urethral stricture is a scar of the subepithelial tissue of the corpus spongiosum that constricts the urethral lumen. As the constriction increases, obstruction occurs and leads to symptoms which may be related to the obstruction or secondary to it(1). (Figure 1).